Copepod supplementation as a live food improved growth and survival of Asian seabass Lates calcarifer larvae. (12th September 2018) - Rasdi, Nadiah W.; Qin, Jian G.
Abstract: The copepod Cyclopina kasignete was supplemented to the Asian seabass Lates calcarifer larvae to evaluate its potential use as a live food supplement during larval rearing. Initial larval feeding began with sole rotifers as a live food from 3 to 7 days post hatch (DPH) followed by the addition of copepod, Artemia, and their combination from 8 to 21 DPH. Fish were sampled every 5 days to measure growth and food selectivity on 11, 15, 19, and 21 DPH. The larvae that were fed the combination diets involving copepods resulted in better growth, survival, and increased the essential fatty acid contents of eicosapentaenoic acid and docosahexaenoic acid. In terms of food selectivity, seabass larvae selected copepods over rotifers and Artemia for feeding. This study indicates that the potential use of copepod as a supplementary live food can improve larval fish performance and thus overcome low survival and slow growth in fish larval aquaculture. The present study demonstrates that the nutritional value of seabass larvae was improved when fed with diets involving copepods. Our finding highlights the importance of incorporating copepods into the feeding regimes for seabass larvae, which may be applicable to the culture of fish larvae for other species.